The toxicity of zinc oxide on blood factors of Huso huso and Cyprinus carpio - Shahedeh Mohammadnezhad; Fatemeh Shariati; Abdolkarim Keshavarz; Habib Vahabzadeh (Islamic Azad University, 2016)
In this research, acute toxicity (LC) of zinc oxide nanoparticle on Beluga (Huso huso) and common carp (Cyprinus carpio) was studied. The experiment was conducted using the Organization for Economic Co-operation and Development (No. 202) method. For both species, 96hLC10 was determined to be more than 200 mg/l. To assess the effects of zinc oxide nanoparticles on blood factors, leukocyte index count (Lymphocyte, Monocytes, Neutrophils, Eosinophil, and Basophils) was performed, and the results were analyzed using IBM SPSS software version. According to the results and based on the ANOVA test, there is no significant difference among mean values of leukocyte index responses (p>0.05), and one should note that the amount of lymphocyte had decreased while that of neutrophils and monocytes had increased. Furthermore, with regard to concentration levels, this decrease or increase has not followed a systematic trend. In Beluga based on ANOVA test, there is a significant difference between mean values of lymphocytes and neutrophils (p<0.05). Again, compared to control, lymphocyte count increased while that of neutrophils and eosinophil decreased, and this too, did not follow a systematic trend. Finally, concentration to 200 mg/l ZnO did not cause mortality in Huso huso and Cyprinus carpio. Eventually, decline of body resistance against nano zinc oxide was observed in these species through blood cells study.